A new fragile digital watermarking technique for a PDF digital Holy Quran - Alahmad, Mohammad; Alshaikhli, Imad Fakhri Taha; Alduwaikh, Amal E. (2013)
Digital media manipulation has become easily performed at personal level with the rapidly growth of Technology. Presenting an issue of protecting digital media integrity. Watermarking has become a popular solution for copyright and integrity issues. This paper presents an invisible fragile watermarking technique for protecting the integrity of a PDF Digital Holy Quran. This watermark is generated using DCT algorithm for feature extracting along with a Gear hash function to provide tampering detection.